1981
DOI: 10.1073/pnas.78.10.6168
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of the first constant region domain and the hinge region of the delta heavy chain of human IgD.

Abstract: BiochemistryAmino acid sequence of the first constant region domain and the hinge region of the 6 heavy chain of human IgD ( ABSTRACT We have determined the amino acid sequence of the first constant (C) region domain (C61) and the hinge region of the 6 heavy chain of human IgD WAH and also the sequence of the adjacent COOH-terminal portion of the variable (V) region, including the JH region. Together with the sequence ofthe Fc fragment already reported, this establishes the complete amino acid sequence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Peptides were prepared by digestion with trypsin, chymotrypsin, or Staphylococcus aureus V8 protease (2,3). The aminoterminal CNBr fragment of the 8 chain was resistant to these enzymes and so was digested with pepsin and also cleaved by iodosobenzoic acid or dilute acid (0.03 M HCl).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peptides were prepared by digestion with trypsin, chymotrypsin, or Staphylococcus aureus V8 protease (2,3). The aminoterminal CNBr fragment of the 8 chain was resistant to these enzymes and so was digested with pepsin and also cleaved by iodosobenzoic acid or dilute acid (0.03 M HCl).…”
Section: Methodsmentioning
confidence: 99%
“…However, mounting evidence that this minor class ofcirculating immunoglobulins has a major function as an antigen receptor on the membrane of B lymphocytes (10,11) led us to undertake determination of the complete primary structure of human IgD. We have reported the complete amino acid sequence of the Fc region (2) and of the C81 and hinge regions (3), which together constitute the entire constant (C) region ofthe 8 chain of the myeloma protein WAH. Here, we report the structure ofthe variable (V) region ofthe heavy (H) chain (the VH region), which completes the amino acid sequence of the 8 H chain; in work to be reported separately, we have determined the entire sequence ofthe A light (L) chain, which completes the structure of a human IgD molecule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The heavy chains of IgD, IgA and the IgGs all have three C H domains and a hinge region that joins the Fab regions to the Fc. Putnam et al, (1980) have suggested that the hinge region exon evolved by mutation of the C H 2 domain-encoding exon, and Parvari et al (1988) pointed out that the COOH-terminal residues (cysteineproline) of the chicken C H 2 domain can be found at the COOH ends of many mammalian hinge regions. Recent modelling studies of Padlan (personal communication) have placed the hinge region of the IgE heavy chain at the C H 2 /C H 3 domain boundary; the IgE C H 2 /Cm interdomain has parallel disulphide bonds at its boundaries and shows considerable segmental flexibility, believed to be important in the effector processes arising from the interaction between the molecule and Fc e receptors (Helm et al, 1991).…”
mentioning
confidence: 99%
“…(iii) JA is more closely related to JH than it is to JK. EXPERIMENTAL PROCEDURES To determine the complete amino acid sequence of the A L chain we used the methods of automated sequence analysis described for the 6 chain (9,(15)(16)(17)(18). These were combined with a strategy based on the power of HPLC (high-performance liquid chromatography) to purify large peptides.…”
mentioning
confidence: 99%